2017
DOI: 10.1080/21541264.2017.1381795
|View full text |Cite
|
Sign up to set email alerts
|

SHPRH as a new player in ribosomal RNA transcription and its potential role in homeostasis of ribosomal DNA repeats

Abstract: There are hundreds of copies of rDNA repeats in mammalian chromosomes and the ratio of active, poised, or inactive rDNA is regulated in epigenetic manners. Recent studies demonstrated that a post-DNA replication repair enzyme, SHPRH affects rRNA transcription by recognizing epigenetic markers on rDNA promoters and unveiled potential links between DNA repair and ribosome biogenesis. This study suggests that SHPRH could be a link between mTOR-mediated epigenetic regulations and rRNA transcription, while concomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Hence, it was concluded that this represents a poised state, which is transcriptionally silent but remains permissive for transcriptional activation. Recently, the helicase SNF2 histone linker PHD RING helicase (SHPRH), a functional homolog of yeast Rad5, has been suggested to be responsible for sensing of poised rDNA promoters and for localizing Pol I to these promoters via interaction with H3K4me and H3K4me2 (Lee et al 2017 , 2018 ). Furthermore, the authors identified the mammalian target of rapamycin (mTOR) pathway implicated in this process, thus linking gene activation with environmental cues.…”
Section: Nucleolar Morphology and Regulation Of Gene Transcriptionmentioning
confidence: 99%
“…Hence, it was concluded that this represents a poised state, which is transcriptionally silent but remains permissive for transcriptional activation. Recently, the helicase SNF2 histone linker PHD RING helicase (SHPRH), a functional homolog of yeast Rad5, has been suggested to be responsible for sensing of poised rDNA promoters and for localizing Pol I to these promoters via interaction with H3K4me and H3K4me2 (Lee et al 2017 , 2018 ). Furthermore, the authors identified the mammalian target of rapamycin (mTOR) pathway implicated in this process, thus linking gene activation with environmental cues.…”
Section: Nucleolar Morphology and Regulation Of Gene Transcriptionmentioning
confidence: 99%
“…Its associated gene symbol is a tumor suppressor gene named SHPRH, which could be found in glioblastoma and could affect genomic integrity. 10,11 Our data illustrated that high expression hsa_circ_0005075 was observed in CRC samples and cells by quantitative real-time PCR (qRT-PCR), and high expression of hsa_circ_0005075 was correlated with clinical pathological characteristics and survival rate. Moreover, proliferation and invasion of CRC cells were impacted by the expression level of hsa_circ_0005075.…”
Section: Introductionmentioning
confidence: 81%
“…SHPRH , a cancer suppressor gene, functions in DNA repair and regulates ribosomal RNA transcription 2325. Circ-SHPRH is a circular RNA derived from SHPRH exons via back-splicing.…”
Section: Discussionmentioning
confidence: 99%